Sound-production mechanism in Pomatoschistus pictus - Parmentier, Eric (2017)
Fish acoustic signals play a major role during agonistic and reproductive interactions. Among the sound-generating fish, Gobiidae, a large fish family with 1866 valid species, is one of the most studied groups of acoustic fishes, with sound production being documented in a number of species. Paradoxically, the sound-producing mechanism remains poorly studied in this group. The painted goby, Pomatoschistus pictus, produces two distinct sounds called drums and thumps. A combination of morphological and experimental analyses involving high-speed videos synchronized with sound recordings supports that drums are produced during lateral head movements involving at least the alternate contractions of the levator pectoralis muscles originating on the skull and inserting on the pectoral girdle. These movements are reported in many Gobiidae species, suggesting the pectoral-girdle-based mechanism is common in the family and could have evolved from locomotory movements.